Peranan Perempuan Bali Dalam Meningkatkan Pendapatan Rumah Tangga Melalui Penjualan Sarana Upakara (Studi Kasus Pedagang Sarana Upakara di Pasar Badung) - Andriani, Kadek Della; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
Humans were created with  two different  male and female. However, in Bali we often encounter discrimination between men and women in terms of employment. This research aims to determine the role of Balinese women in household incomes through the sales of the property of upakara yadnya . This research using the primary data. The analysis technique used is the technique of descriptive statistical analysis and multiple linear regression analysis. The results of the study using descriptive statistics show that Balinese women has a major role in increasing household income. While the working time variable, work experience and capital are partial and simultaneously have a positive and significant effect on household income of the salesman of upakara yadnya in Badung’s market. Keywords: working time, working experiences, capital and household incomes